Social Capital in Determining Recipients of The Village Fund Cash Assistance (BLT-DD) in Woro Village, Indonesia - Susanti, Afrilia Ira; Prayitno, Gunawan; Adrianto, Dimas Wisnu (Fakultas Teknik Universitas Brawijaya, 2024)
Village Fund Cash Assistance (BLT-DD) was reintroduced in 2020 as a program by the Indonesian Government to reduce the negative impacts of COVID-19. BLT-DD is distributed to poor people who meet certain eligibility requirements in many rural areas in Indonesia, including Woro Village in Bojonegoro Regency. In implementing the BLT-DD program, strong social capital is needed in determining the target recipients of the program. The research aims to analyze community social capital in the process of selecting applicants for the BLT-DD program. Focus on analyzing social capital element factors, namely trust, networks and norms using Structural Equation Modeling analysis based on Partial Least Square (SEM-PLS) analysis.. Determining the sample using purposive sampling technique and calculations based on the Kirche Morgan formula obtained a sample of 95 respondents. The results of research on social capital show that trust is the most influential element of the social capital of the Woro Village community. However, there are other elements of social capital, namely networks and norms, that need to be increased. So that overall social capital can support program implementation effectively and on target in supporting post-COVID-19 village recovery.